PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN, CORPORATE GOVERNANCE DAN TRANSAKSI PIHAK BERELASI TERHADAP DAYA INFORMASI AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Cicilia, Cicilia; Lindrawati, Lindrawati (Jurnal Akuntansi Kontemporer, 2014)
Financial report is a summary of the corporate business transaction that indicates conditions or financial position at any given moment. The information contained in the financial statements utilized by users for taking decisions, so there is no confusion in taking decisions by investors, the financial statements must be qualified. A quality financial reports is a report containing figures which have informa-tiveness of accounting number that is helpful for the users to make decisions. Any doubts the quality of the financial statements due to the possibility of modifications to the figures in the financial statements which could lead to investors is wrong in taking investment decisions. This study aims to test empirically regarding the influence of the structure of ownership of the firm, corporate governance and the closely related party transactions against the accounting information resource Design research is quantitative research with manufacturing companies listed on the Indonesia stock exchange in 2009-2011 as research objects. The technique was purposive sam-pling. Data analysis technique used was multiple linear regression. The result showed that the ownership structure consisting of con-centrated ownership structure positive significant to control the informativeness of accounting number but family control did not in-fluence significantly to the informativeness of accounting number. Corporate governance consisting of independent commissioner and audit comitte have no impact on the informativeness of accounting number. the closely related party transactions have no impact against the informativeness of accounting number.